Perencanaan Sistem Pendidikan Islam: Pandangan Undang-Undang Sisdiknas No. 20 Tahun 2003 - Syabilah Marshanda; Syamsiah Syahruddin; Dias Akhwatun Nuha (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This article discusses the planning of the Islamic education system in the view of the Ecclesiastes No. 20 Year 2003. Islamic education is understood as a process of change and Islamic values through the process of self-development, with the aim of achieving the perfection of life. In any activity, planning is an important and strategic component that serves as a guideline when conducting an activity in order to a goal, goal, or goal expected.The author searches for information about the Islamic Education System Planning: A View of the Law No. 20 of 2003 through a variety of library information, including books and scientific journals. As one of the elements of the national education system, Islamic education has the right to exist and to have the opportunity to advance and thrive in Indonesia as a form of fulfilling the educational needs of Muslim communities that are majority citizens because Islamic religion education is an integral part of the National Education System. The State has an obligation or responsibility to promote Islamic religious education. In the Islamic educational system, planning serves as a basic benchmark, direction and guidance in determining decisions, in conducting and directing educational activities, in improving the quality of education in accordance with the national educational development as the realization of educational goals in order to create an individual with a Muslim personality based on the values of Islamic teachings that originate from the Quran and the Sunnah.